2018
DOI: 10.1002/jor.23895
|View full text |Cite
|
Sign up to set email alerts
|

Gait mechanics and tibiofemoral loading in men of the ACL‐SPORTS randomized control trial

Abstract: The risk for post-traumatic osteoarthritis is elevated after anterior cruciate ligament reconstruction (ACLR), and may be especially high among individuals with aberrant walking mechanics, such as medial tibiofemoral joint underloading 6 months postoperatively. Rehabilitation training programs have been proposed as one strategy to address aberrant gait mechanics. We developed the anterior cruciate ligament specialized post-operative return-to-sports (ACL-SPORTS) randomized control trial to test the effect of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…To ameliorate alterations in knee biomechanics, clinicians may consider neuromuscular training as a potential intervention, as recent work from Nagelli and colleagues 38 demonstrated that a 12-session neuromuscular training program improved sagittal plane knee biomechanics during landing in individuals approximately 8 months after ACLR. However, in a recent study, Capin and collagues 6 found that a rehabilitation program that included neuromuscular and secondary-injury prevention exercises did not improve gait mechanics over time in individuals after ACLR. An important area of future work is to better understand what specific variables should be prioritized or targeted with neuromuscular training interventions to better improve movement patterns in this patient population.…”
Section: Discussionmentioning
confidence: 94%
“…To ameliorate alterations in knee biomechanics, clinicians may consider neuromuscular training as a potential intervention, as recent work from Nagelli and colleagues 38 demonstrated that a 12-session neuromuscular training program improved sagittal plane knee biomechanics during landing in individuals approximately 8 months after ACLR. However, in a recent study, Capin and collagues 6 found that a rehabilitation program that included neuromuscular and secondary-injury prevention exercises did not improve gait mechanics over time in individuals after ACLR. An important area of future work is to better understand what specific variables should be prioritized or targeted with neuromuscular training interventions to better improve movement patterns in this patient population.…”
Section: Discussionmentioning
confidence: 94%
“…Subjects showing greater magnitude of gait asymmetries in the first months may present similar imbalances when returning to running [25] and subsequently to sport [26], with walking adaptations detected up to 2 years after surgery [29]. Moreover, it is known that kinematic and kinetic alterations after ACL injury and surgery affect lower limbs bilaterally [30][31][32], with these alterations also occurring in the uninjured leg during walking activities [16,17,26,33]. This is further confirmed by our results showing significant changes over time in the non-operated leg, especially in the EG (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the midand long-term perspective, this is often associated with persistent thigh muscles weakness in the operated limb, thereby leading to a side-to-side asymmetry that alters normal knee and lower limb mechanics during daily motion [14,15]. For instance, during walking and functional tasks, reductions in the peak of knee flexion angle, external knee flexion moment, vertical impulse as well as posterior peak of ground reaction force have been observed in the operated limb of patients with ACL lesion and reconstruction [16][17][18][19]. Accordingly, after the reconstruction, it is well known that reaching a complete range of motion is one of the main goals of the early rehabilitation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients reached these return-to-sport milestones and subsequently were cleared to begin a return-to-sport progression (pending clearance from the surgeon); all returned to sport within 2 years, most to the same sport level. 9,10…”
Section: Methodsmentioning
confidence: 99%
“…4,10,14 Yet, clinically meaningful gait asymmetries 19 persist well beyond return-to-sport clearance, up to 5 years after ACLR. 10,24,32,33 While quadriceps strength is associated with aberrant gait mechanics early after ACLR, 36 it is not clear if that relationship persists after return-to-sport training or if other factors drive persistent gait asymmetries. The association between symmetry in isometric quadriceps strength and aberrant gait mechanics among patients who have undergone rehabilitation and return-to-sport training after ACLR is unknown.…”
mentioning
confidence: 99%